The effectiveness of speed, agility, quickness training vs high-intensity interval training in improving speed and agility on badminton players - Sapto Wibowo; Oce Wiriawan; Anindya Maratus Sholikhah; Achmad Syaifudin; Yuri Pamungkas; Lilik Herawati; Gadis Meinar Sari; Dodi Wirawan Irawanto; Radityo Putro Handrito; Sapto Adi; Supriyadi Supriyadi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Badminton is a fast-paced racket sport which requires player to possess quick reaction, high-speed hitting ability, and rapid movement. These abilities are related to speed and agility which are one of the essential motor demands in badminton.